Approximating perfect recall when model checking strategic abilities - Belardinelli,F; Lomuscio,A; Malvone,V (AAAI, 2018)
We investigate the notion of bounded recall in the contextof model checking AT L∗and AT L specifications in multiagent systems with imperfect information. We present a novelthree-valued semantics for AT L∗, respectively AT L, underbounded recall and imperfect information, and study the corresponding model checking problems. Most importantly, weshow that the three-valued semantics constitutes an approximation with respect to the traditional two-valued semantics.In the light of this we construct a sound, albeit partial, algorithm for model checking two-valued perfect recall via itsapproximation as three-valued bounded recall.